Uji Aktivitas Anti Bakteri Dari Formula Ekstrak Daun Ciplukan (Physalis angulata L.) dan Batang Kayu Manis (Cinnamomum burmannii) Secara In Vitro Test - Fuad Muzakky; Malika Ilma Alkautsar; Anni Humayroh Syawalia; Nabila Mirza Azizi; Subhan Rullyansyah (Universitas Muhammadiyah Surabaya, 2021)
Ciplukan leaves (Physalis angulata L.) and Cinnamon (Cinnamomum burmannii) are one of medicinal plants that contain antibacterial active compounds. This study aims to determine the antibacterial activity of the combination formula between extracts of ciplukan leaves and cinnamon sticks against the growth of Staphylococcus aureus bacteria in Vitro. Ciplukan leaves (Physalis angulata L.) and cinnamon (Cinnamomum burmannii) were extracted by the maceration method with 70% ethanol. Ciplukan leaf extract (Physalis angulata L.) and cinnamon (Cinnamomum burmannii) were tested against Staphylococcus aureus bacteria using the good method by measuring transmittance on a spectrophotometer at a wavelength of 580 nm with 3 repetitions, 100 ppml standard Septromycin solution as control positive and aquadest as a negative dick. Inhibition zone diameter of ciplukan leaf extract (Physalis angulata L.) x̄ = 12.46 mm, Cinnamon Extract (Cinnamomum burmannii) x̄ = 18.93 mm, while in the formulation group x̄ = 22.45 mm. One-way analysis of variance (ANOVA) of these data compared with Streptomycin activity (positive control) showed significant inhibitory activity by the formulated extract against S. aureus. Keywords: Antibacterial, Staphylococcus aureus, Ciplukan leaves (Physalis angulata L.) and Cinnamon (Cinnamomum burmannii)